Buddy Schemes between Refugees and Volunteers in Germany: Transformative Potential in an Unequal Relationship? - Stock, Inka (2019)
Since 2016, many German citizens have participated in so-called ‘buddy schemes’ in which volunteers provide personalised support to refugees to help them build their new lives in Germany. These relationships are characterised by ethnic, gender, and age differences between the two parties. This article looks at buddy schemes from the perspective of both volunteers and refugees and investigates whether their relationships open up spaces for transformative citizenship practices, or rather reinforce exclusionary discourses. Drawing on feminist theories of care, the article describes how volunteers and refugees attach meaning to their activities and roles in the relationship. On the one hand, values attached to caring relationships, such as emotional closeness, trust, and respect, contribute to migrants’ heightened sense of self-esteem and autonomy and foster volunteers’ sense of responsibility for fighting against inequality. On the other hand, both parties enter into particular logics of care that potentially reinforce power hierarchies between them. These ambiguous dynamics influence the possibility of transformative citizenship practices on both sides. While some volunteers and refugees develop and take a critical stance on restrictive migration policies in their relationships with others, others reinforce their exclusionist viewpoints on who deserves to be helped and by whom.